Using GAMS for agricultural policy analysis - Minot, Nicholas (International Food Policy Research Institute, 2009)
The objective of this training module is to explain how to use GAMS to construct, calibrate, and modify agricultural sector models in order to simulate the effect of alternative policies or other events affecting agricultural markets. In particular, the course aims to train the participants in the following skills: * determining whether an agricultural sector model is appropriate for a given research question; * selecting the scale of the model in terms of commodities, markets, and time periods; * constructing the model in GAMS using available data; * running simulations of alternative policies and events; * revising the model in response to new information; and * documenting and describing the results of simulations. Although the course does not attempt to cover agricultural economics and international trade in depth, it does provide a quick review of concepts to explain the logic behind the components of agricultural sector models. It should be noted that this course is not a lecture course, but rather it is a semi-structured hands-on workshop in which trainees will use computers to learn different methods of analyzing data. The course starts out with very simple models and gradually introduces new concepts and new commands to develop a multi- market spatial equilibrium model that represents four commodities and six regions, as well as internal trade and international trade. This model is called SDP4 and is shown in Annex 1 of this guide.